Interprofessional Research on the Inclusion of Young Children with Developmental Disabilities as they Transition from Preschool to Elementary School - Villeneuve, Michelle; Chatenoud, Celine; Minnes, Patricia; Perry, Adrienne; Hutchinson, Nancy L.; Frankel, Elaine B.; Loh, Alvin; Dionne, Carmen; Weiss, Jonathan; Versnel, Joan; et al. (Canadian Journal of Education/Revue canadienne de l’éducation, 2013)
This paper is submitted in response to the call for papers on inclusion. Despite recognition of the importance of parent and interprofessional collaboration to enable meaningful inclusion outcomes for young children with developmental disabilities in education contexts, limited research has investigated how parents, educators and healthcare providers actually collaborate to support inclusion goals. Moreover, research has not examined inclusion from the diverse perspectives of stakeholders across early childhood, healthcare, and education sectors. This paper describes the work of HELPS Inc, a Canadian research project describing Health, Education, and Learning Partnerships Promoting Social Inclusion of young children with developmental disabilities.